2021
DOI: 10.1038/s41612-021-00174-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of cloud-radiative feedbacks on tropical precipitation extremes

Abstract: Although societally important, extreme precipitation is difficult to represent in climate models. This study shows one robust aspect of extreme precipitation across models: extreme precipitation over tropical oceans is strengthened through a positive feedback with cloud-radiative effects. This connection is shown for a multi-model ensemble with experiments that make clouds transparent to longwave radiation. In all cases, tropical extreme precipitation reduces without cloud-radiative effects. Qualitatively simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 73 publications
4
10
0
Order By: Relevance
“…They found that removing the ACRE above 600 hPa led to a reduction in the strength of the Hadley and Walker circulations. Similar results have been obtained in more recent studies utilizing updated GCMs, which have also noted the role of ACRE in determining the width of the ITCZ, reducing the double‐ITCZ bias, and strengthening the precipitation associated with various tropical phenomena (Albern et al., 2018; Benedict et al., 2020; Harrop & Hartmann, 2016; Li et al., 2015; Medeiros et al., 2021; Popp & Silvers, 2017; Voigt & Albern, 2019). For a recent review of the interactions between clouds, radiation, and atmospheric circulations, see Voigt et al.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…They found that removing the ACRE above 600 hPa led to a reduction in the strength of the Hadley and Walker circulations. Similar results have been obtained in more recent studies utilizing updated GCMs, which have also noted the role of ACRE in determining the width of the ITCZ, reducing the double‐ITCZ bias, and strengthening the precipitation associated with various tropical phenomena (Albern et al., 2018; Benedict et al., 2020; Harrop & Hartmann, 2016; Li et al., 2015; Medeiros et al., 2021; Popp & Silvers, 2017; Voigt & Albern, 2019). For a recent review of the interactions between clouds, radiation, and atmospheric circulations, see Voigt et al.…”
Section: Introductionsupporting
confidence: 82%
“…Recently, Benedict et al (2020) used a set of mechanism-denial experiments to show that removing the ACRE weakens the MJO. Medeiros et al (2021) also found that removing cloud radiative feedbacks weakens tropical precipitation by reducing the frequency of extreme precipitation events. Ruppert et al (2020) have shown that a similar feedback promotes the intensification of tropical cyclones.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The longwave ACRE has been identified as an important feedback mechanism in the context of the persistence of convective self‐aggregation, the initial development of tropical cyclones, and the Madden‐Julian Oscillation (Arnold & Randall, 2015; Benedict et al., 2020; Bretherton et al., 2005; Chikira, 2014; Emanuel, 2019; Khairoutdinov & Emanuel, 2018; Medeiros et al., 2021; Ruppert et al., 2020; Wing et al., 2017; Wolding et al., 2016). The longwave ACRE can be a strong localized atmospheric heating that induces a thermally direct circulation connecting humid and dry regions.…”
Section: Introductionmentioning
confidence: 99%
“…However, Li et al (2015) found that CRE can decrease precipitation in the tropics but increase it at middle-to-high latitudes. Recently, Medeiros et al (2021) reported that extreme precipitation over tropical ocean is strengthened by CRE. While mean precipitation and large-scale circulation can be affected by removing CRE, it is unclear how precipitation, especially extreme precipitation, will respond if radiative-convective interactions are disabled.…”
mentioning
confidence: 99%